2020
DOI: 10.3390/jcm9061997
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Geometry and Replacement Fibrosis Detected by cMRI Are Associated with Major Adverse Cardiovascular Events in Nonischemic Dilated Cardiomyopathy

Abstract: To investigate the relationship between left ventricular (LV) long-axis strain (LAS) and LV sphericity index (LVSI) and outcomes in patients with nonischemic dilated cardiomyopathy (NIDCM) and myocardial replacement fibrosis confirmed by late gadolinium enhancement (LGE) using cardiac magnetic resonance imaging (cMRI), we conducted a prospective study on 178 patients (48 ± 14.4 years; 25.2% women) with first NIDCM diagnosis. The evaluation protocol included ECG monitoring, echocardiography and cMRI. LAS and LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The extent of myocardial brosis is an important determinant of prognosis. In STEMI, transmural MF usually leads to irreversible ventricular remodeling and heart failure, and is also the pathological basis for arrhythmias, and is generally considered to be associated with sudden cardiac death (29)(30)(31)(32). Nguyen et al (33) found that the severity of myocardial brosis was signi cantly correlated with the frequency of ventricular arrhythmias (r = 0.83, P< 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of myocardial brosis is an important determinant of prognosis. In STEMI, transmural MF usually leads to irreversible ventricular remodeling and heart failure, and is also the pathological basis for arrhythmias, and is generally considered to be associated with sudden cardiac death (29)(30)(31)(32). Nguyen et al (33) found that the severity of myocardial brosis was signi cantly correlated with the frequency of ventricular arrhythmias (r = 0.83, P< 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Late-gadolinium enhancement (LGE) is used in evaluating myocardial fibrosis [ 113 , 114 ], and data from studies are contradictory [ 115 ]. LGE is infrequently observed in patients treated with trastuzumab and anthracyclines, and its absence doesn’t exclude myocardial fibrosis [ 116 , 117 ].…”
Section: Diagnosis Methods Of Chemotherapy-induced Cardiotoxicity In Gi Cancersmentioning
confidence: 99%
“…Cardiac fibrosis is one of the hallmarks of DCM and is typically observed in 40–60% of cases [ 5 , 6 ]. Fibrosis significantly contributes to the progression of HF symptoms and functional impairment; it also increases the risk of re-entrant arrhythmias, leading to increased morbidity and mortality in DCM [ 7 ].…”
Section: Introductionmentioning
confidence: 99%